KEANEKARAGAMAN SERANGGA HAMA DAN SERANGGA PREDATOR PADA BUNGA TANAMAN BELIMBING MANIS (Averrhoa Carambola) VARIETAS BANGKOK MERAH - Novita Endah Ariani; Wiwin Windriyanti; Yenny Wuryandari (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Sweet starfruit plant is one type of horticulture plant that has a 60% rate of flowering caused by pests on the flower so that there is a decrease in sweet star fruit production. This study aims to determine the diversity of pest and predator insects in sweet starfruit flowers and the influence of environmental factors (temperature and humidity) on pests and predator insect visits on sweet starfruit flowers. Observations were made in 3 time periods, starting at 08.00-17.00 WIB for 20 days. The number of plants used in this study were 40 starfruit trees, in one day the observation needed two starfruit trees, for each tree an 30-minute observation was made. Observations were made using sweep net, yellow sticky trap and visually. The recorded environmental physics parameters consist of air temperature and humidity. Based on the results of the study there are 4 types of insect pests and 2 types of sweet flower starfruit predator insect predators. Shannon-Wiener index analysis of insect pests shows the category of low diversity index, low dominance index and low evenness index. Predatory insects show the category of low diversity index, high dominance index and even distribution index.